BNN27, a 17-Spiroepoxy Steroid Derivative, Interacts With and Activates p75 Neurotrophin Receptor, Rescuing Cerebellar Granule Neurons from Apoptosis - Pediaditakis, Iosif; Kourgiantaki, Alexandra; Prousis, Kyriakos C.; Potamitis, Constantinos; Xanthopoulos, Kleanthis P.; Zervou, Maria; Calogeropoulou, Theodora; Charalampopoulos, Ioannis; Gravanis, Achille (Frontiers in Pharmacology, 2016)
Neurotrophin receptors mediate a plethora of signals affecting neuronal survival. The p75 pan-neurotrophin receptor, controls neuronal cell fate after its selective activation by immature and mature isoforms of all neurotrophins. It also exerts pleiotropic effects interacting with a variety of ligands in different neuronal or non-neuronal cells. In the present study, we explored the biophysical and functional interactions of a blood-brain-barrier (BBB) permeable, C17-spiroepoxy steroid derivative, BNN27, with p75NTR receptor. BNN27 was recently shown to bind to NGF high-affinity receptor, TrkA. We now tested the p75NTR-mediated effects of BNN27 in mouse Cerebellar Granule Neurons (CGNs), expressing p75NTR, but not TrkA receptors. Our findings show that BNN27 physically interacts with p75NTR receptors in specific amino-residues of its extracellular domain, inducing the recruitment of p75NTR receptor to its effector protein RIP2 and the simultaneous release of RhoGDI in primary neuronal cells. Activation of the p75NTR receptor by BNN27 reverses serum deprivation-induced apoptosis of CGNs resulting in the decrease of the phosphorylation of pro-apoptotic JNK kinase and of the cleavage of Caspase-3, effects completely abolished in CGNs, isolated from p75NTR null mice. In conclusion, BNN27 represents a lead molecule for the development of novel p75NTR ligands, controlling specific p75NTR-mediated signaling of neuronal cell fate, with potential applications in therapeutics of neurodegenerative diseases and brain trauma.